PEMANFAATAN DAN OPTIMALISASI LAHAN KERING UNTUK PENGEMBANGAN BUDIDAYA TANAMAN PALAWIJA DI DESA PUDAY KECAMATAN WONGEDUKU KABUPATEN KONAWE PROVINSI SULAWESI TENGGARA - Helviani Helviani; Aan Wilhan Juliatmaja; Doddy Ismunandar Bahari; Masitah Masitah; Husnaeni Husnaeni (LPPM Universitas Flores, 2021)
Land is one of the potential natural resources to be developed optimally to increase local revenue. Based on the availability of water, land is grouped into two major groups, which are wetland and dry land (upland). The use of dry land for agriculture is often ignored by policy makers. Problems in dry land management vary in each region, both technical and socio-economic aspects. However, with the right strategy and technology, these problems can be overcome. Efforts to manage dry land to increase food production face problems, including steep slopes, low soil fertility, and water shortages. These problems need to be overcome by applying the right technology. Dry land management technology is available, including management of soil fertility, soil conservation, land rehabilitation, and efficient management of water resources. The problem is the weak dissemination of innovative technology to farmers and the slow adoption of this technology. Utilization of dry land to increase food production requires appropriate planning and strategies.